Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament Melalui Permainan Invasi terhadap Self Satisfaction Siswa - Ahmad Nauval Favian; Agus Mahendra; Mukhlisin (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to evaluate the impact of implementing the Team Games Tournament (TGT) cooperative learning model, combined with an invasion game, on students’ levels of self-satisfaction and playing skills in physical education classes. The study employed a quasi-experimental approach using a Nonequivalent Control Group Design, involving 54 sixth-grade students from SD Negeri 065 Cihampelas in Bandung, who were divided into an experimental group and a control group. The experimental group received TGT-model instruction through handball games over 12 sessions, while the control group received conventional instruction. Data analysis used the Wilcoxon test to examine changes within groups and the Mann–Whitney U test to compare the two groups. The results of the Wilcoxon test indicated a significant increase between the pretest and posttest for both variables (p < 0.05). Furthermore, the results of the Mann–Whitney U test showed significant differences between the experimental and control groups on the variables of self-satisfaction (Z = -6.317; p < 0.001) and playing skills (Z = -6.372; p < 0.001). Additionally, the experimental group achieved an N-Gain score of 71.19% for self-satisfaction and 81.73% for playing skills, indicating an effectiveness level ranging from effective to highly effective. Thus, it can be concluded that the implementation of the Team Games Tournament model through the invasion game is effective in improving self-satisfaction and playing skills among elementary school students. Keywords: Playing Skills, Invasion Games, Elementary School, Self-Satisfaction, Team Games Tournament (TGT)